Exploring medical student perceptions of a video-modified Peyton’s 4-step technique for teaching spinal and neurological examinations - Ramy Sherif; Ewan John; Michael John Haydon McCarthy (Medical Education Online)
Background Peyton’s 4-step technique is a highly recognized framework for teaching practical procedures. This study introduces a unique video-modified adaptation of the technique for teaching clinical examination and evaluates medical students’ perceptions, identifying key areas for enhancement.Methods A cross-sectional study was conducted with 606 second-year medical students, utilizing an online questionnaire to assess their perceptions of the modified teaching method. Responses were measured using a 5-point Likert scale, with 354 students providing feedback.Results Findings revealed significant improvements in student confidence following the video-modified examination session (p-value <0.05). The method was widely accepted by participants, who also provided constructive feedback for refining the teaching approach.Conclusions The video-modified Peyton’s 4-step technique was perceived by students as a well-structured and engaging method for learning spinal and neurological examinations. Its adaptability to small group settings and integration of video-based instruction were well received and considered beneficial for understanding the procedural steps. While students reported increased confidence, this finding should be interpreted with caution given the cross-sectional design of the study. Incorporating this framework into medical curricula may enhance the delivery of clinical skills training, and future research should explore its impact through longitudinal and comparative studies.